Dried Blood Spot Sampling to Assess Rifampicin Exposure and Treatment Outcomes among Native and Non-Native Tuberculosis Patients in Paraguay: An Exploratory Study - Samiksha Ghimire; Gladys Molinas; Arturo Battaglia; Nilza Martinez; Luis Gómez Paciello; Sarita Aguirre; Jan-Willem C. Alffenaar; Marieke G. G. Sturkenboom; Cecile Magis-Escurra (MDPI AG, 2023)
The aim of this study was to evaluate the difference in drug exposure of rifampicin in native versus non-native Paraguayan populations using dried blood spots (DBS) samples collected utilizing a limited sampling strategy. This was a prospective pharmacokinetic study that enrolled hospitalized tuberculosis (TB) patients from both native and non-native populations receiving oral rifampicin 10 mg/kg once-daily dosing. Steady-state DBS samples were collected at 2, 4, and 6 h after intake of rifampicin. The area under the time concentration curve 0-24 h (AUC0-24) was calculated using a Bayesian population PK model. Rifampicin AUC0-24 < 38.7 mg*h/L was considered as low. The probability of target attainment (PTA) was calculated using AUC0-24/MIC > 271 as a target and estimated MIC values of 0.125 and 0.25 mg/L. In total, 50 patients were included. Native patients (n = 30) showed comparable drug exposure to the non-natives (n = 20), median AUC0-24 24.7 (17.1-29.5 IQR) and 21.6 (15.0-35.4 IQR) mg*h/L (p = 0.66), respectively. Among total patients, only 16% (n = 8) had a rifampicin AUC0-24 > 38.7 mg*h/L. Furthermore, PTA analysis showed that only 12 (24%) of the patients met a target AUC0-24 /MIC ≥ 271, assuming an MIC of 0.125 mg/L, which plummeted to 0% at a wild-type MIC of 0.25 mg/L. We successfully used DBS and limited sampling for the AUC0-24 estimation of rifampicin. Currently, our group, the EUSAT-RCS consortium, is preparing a prospective multinational, multicenter phase IIb clinical trial evaluating the safety and efficacy of high-dose rifampicin (35 mg/kg) in adult subjects using the DBS technique for AUC0-24 estimation.